2020
DOI: 10.1016/j.btre.2020.e00567
|View full text |Cite
|
Sign up to set email alerts
|

Safety and bioactive potential of nanoparticles containing Cantaloupe melon (Cucumis melo L.) carotenoids in an experimental model of chronic inflammation

Abstract: Highlights Carotenoids present anti-inflammatory effects in healthy and overweight adults. Nanotechnology can enhance carotenoid's bioactive potential. Nanoparticles loaded with carotenoids from Cantaloupe melon were used in obese rats. Animals receiving the nanoparticles showed no signs of toxicity. Animals treated with nanoparticles had organs better aspect compared to untreated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 33 publications
(36 reference statements)
2
16
0
Order By: Relevance
“…Nanoparticles containing the crude extract rich in carotenoids from the cantaloupe melon pulp in porcine gelatin (EPG) have already been produced by Medeiros et al and Oliveira et al In this study, EPG showed the same physicochemical characteristics and incorporation efficiency of carotenoids demonstrated by Medeiros et al, Medeiros et al, and Oliveira et al even with the obtainment of new batches, which effectively contributed to the investigations in the present study. These findings showed that the replicated method used in this study achieved the desired characteristics, overcoming the difficulties related to reproducibility in obtaining nanoparticles.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Nanoparticles containing the crude extract rich in carotenoids from the cantaloupe melon pulp in porcine gelatin (EPG) have already been produced by Medeiros et al and Oliveira et al In this study, EPG showed the same physicochemical characteristics and incorporation efficiency of carotenoids demonstrated by Medeiros et al, Medeiros et al, and Oliveira et al even with the obtainment of new batches, which effectively contributed to the investigations in the present study. These findings showed that the replicated method used in this study achieved the desired characteristics, overcoming the difficulties related to reproducibility in obtaining nanoparticles.…”
Section: Discussionsupporting
confidence: 69%
“…40,41 An effective way to improve these barriers has been to use nanotechnology to promote the encapsulation of these compounds, obtaining engineered nanoparticles based on delivery systems. 42 Nanoparticles containing the crude extract rich in carotenoids from the cantaloupe melon pulp in porcine gelatin (EPG) have already been produced by Medeiros et al 20 and Oliveira et al 21 In this study, EPG showed the same physicochemical characteristics and incorporation efficiency of carotenoids demonstrated by Medeiros et al, 19 Medeiros et al, 20 and Oliveira et al 21 even with the obtainment of new batches, which effectively contributed to the investigations in the present study. These findings showed that the replicated method used in this study 1 Age-appropriate retinol concentration based on Blomhoff et al 29 2 Retinol excess for age based on Blomhoff et al 29 Images of the livers were recorded after immersion in formalin (4%) to evaluate the superficial color.…”
Section: ■ Discussionsupporting
confidence: 65%
See 3 more Smart Citations